Maternal Blood Trace Element Levels in Preeclampsia: Comprehensive Systematic Review and Meta-Analysis - Wening Hapsari; Achmad Januar Er Putra (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Deficit in trace elements was frequent in pregnant women and could lead to preeclampsia development. This meta-analysis aimed to determine calcium, magnesium, zinc, iron, and copper serum levels in preeclampsia women compared to healthy pregnant women. Methods: A systematic search is conducted in PubMed, ScienceDirect, and Google Scholar from inception into March 25th, 2022 using keywords of “(